The target selective neural response--similarity, ambiguity, and learning effects - Hampshire,A; Thompson,R; Duncan,J; Owen,AM (PLoS One, 2008)
A network of frontal and parietal brain regions is commonly recruited during tasks that require the deliberate 'top-down' control of thought and action. Previously, using simple target detection, we have demonstrated that within this frontoparietal network, the right ventrolateral prefrontal cortex (VLPFC) in particular is sensitive to the presentation of target objects. Here, we use a range of target/non-target morphs to plot the target selective response within distinct frontoparietal sub-regions in greater detail. The increased resolution allows us to examine the extent to which different cognitive factors can predict the blood oxygenation level dependent (BOLD) response to targets. Our results reveal that both probability of positive identification (similarity to target) and proximity to the 50% decision boundary (ambiguity) are significant predictors of BOLD signal change, particularly in the right VLPFC. Furthermore, the profile of target related signal change is not static, with the degree of selectivity increasing as the task becomes familiar. These findings demonstrate that frontoparietal sub-regions are recruited under increased cognitive demand and that when recruited, they adapt, using both fast and slow mechanisms, to selectively respond to those items that are of the most relevance to current intentions.